Produccion y descomposicion de la hojarasca en bosques nativos y de Leucaena sp., en Codazzi, Cesar - Bonilla, R.=700 1 Roncallo, B.; Jimeno, J.; Garcia, T.
(Es, En)
Ilus., 32 ref.
Keywords: HOJARASCA FORESTAL; BIOTA; PESO; ORGANISMOS DEL SUELO; NUTRIENTES; SUELO; COLOMBIA; REVISTA CORPOICA